(Re)Configuração da educação por meio da atuação da gestão educacional : contribuições dos conceitos de cooperação e comunidade ética - München, Gabriel (Universidade do Vale do Rio dos Sinos, 2023)
This study aimed to investigate the conceptions of cooperation and ethical community in research and among educational managers in the Municipal Education Network of Tupandi to contemplate their role in the (re)configuration of education. One of the concerns of this research was to delve into the theme of cooperation in relation to the ethical community in contemporaneity, where subjectivities are largely shaped by changes in the world of work, the dynamics of competition, individualization, and the lack of collaboration. Therefore, it is crucial to understand the present moment and its impacts on our ways of being in the world and the groups to which we belong. The objectives of this study were: to understand changes in the world of work and their effect on the lack of cooperation; to comprehend the importance of skill and well-executed work, as well as the relevance of trust in cooperation; to deepen the understanding of the conceptions of cooperation and ethical community and their relationship with educational management. To achieve this, we sought to understand and deepen the concepts of cooperation and ethical community based on the studies of Sennett (2019, 2020, and 2021) and Bauman (2003). The municipality of Tupandi/RS served as the empirical field for this research, and research-training was adopted as the methodological procedure, with the technique of focus groups, conducted with educational managers from the Municipal Education Department and school administrators in the Municipal Education Network. The main results include a conceptual deepening of cooperation and ethical community, as well as its contribution to the field of educational management; time and space management, the importance of diversity, ongoing workplace training as central elements in the reconfiguration of education, and the value of craftsmanship and well-executed work as powerful tools for the development of social skills. As products of this intervention research, we highlight a Letter of Intent from Educational and School Management for the Future of Education in Tupandi, developed in collaboration with the managers from the research-training, and the construction of Phase 2 of the Educational Management Professionalization Program (PPGE).
Keywords: Cooperação; Cooperativismo; Comunidade ética; Artesania; Gestão educacional; Carta de intenções; Cooperation; Cooperativism; Ethical community; Craftsmanship; Educational management; Letter of intentions; ACCNPQ::Ciências Humanas::Educação